Hydrodynamic variations and human activities have influenced sediment fluxes in the pearl river delta since the late holocene - Yang, Xiaoqiang; Wu, Shuang; Shang, Shentang; Chen, Yan (Frontiers in Earth Science, 2023)
Climate change and human activity can both exert a role in the river discharge and sediment load in river deltas when the sea level remains relatively stable. The Pearl River Delta constitutes the metropolitan region of the Guangdong–Hong Kong–Macau Greater Bay Area, and its evolution in the past and future impacts the sustainable development of this region. In this manuscript, a core situated in the northern South China Sea, adjacent to Qiao Island of Zhuhai city in the Pearl River Delta, was selected to investigate the hydrodynamic variation influenced by tropical processes and the sediment flux imposed by human activities. Using paleosecular variations (PSVs) in geomagnetic field correlations constrained by seven radiocarbon ages, an ~2.5 kyr chronology was provided for core sediments ~2.8 m in length. The magnetic fabric results suggest that deposition was influenced by the two types of hydrodynamic-weak energy modulated by El Niño–Southern Oscillation (ENSO) activity and higher energy regulated by high-frequency tropical storms. The cyclic variations in the degree of anisotropy of magnetic susceptibility (P) indicate two periodic changes at approximately 300 and 100 years, which were forced by ENSO activity, while the ratio of lineation with foliation (q value) implies a higher energy flow period of 1.3-1.9 kyr, arising from strong tropical storms. Moreover, the high saturation remanence (SIRM) introduces more sediment flux, which is impacted by growing human activity during the period of 1.0-1.6 kyr.